2016
DOI: 10.1097/mjt.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Prasugrel Compared With Clopidogrel for Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Abstract: Dual antiplatelet therapy comprising aspirin and a P2Y12 inhibitor (clopidogrel, prasugrel, or ticagrelor) is essential to prevent thrombotic complications after percutaneous coronary intervention (PCI). The comparative efficacy between clopidogrel at a higher loading dose (600 mg) and prasugrel is uncertain. The aim of this study was to compare efficacy and safety of clopidogrel (higher loading dose) with prasugrel (loading dose of 60 mg) along with their respective maintenance doses in patients with acute co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…34 Cardiology studies showed that patients who receive prasugrel exhibit major haemorrhages more frequently than patients who receive clopidogrel, especially in patients with previous strokes, elderly patients (more than 75 years) and slim patients (weight lower than 60 kg). 33,35 However, the increased risks associated with prasugrel were not found in other cardiology series, 36,37 Until now, usage of prasugrel in Interventional Neuroradiology 23 (1) cerebrovascular diseases field has been limited 16,[38][39][40][41][42] by the fear of risk of intracranial haemorrhage. While Akbari et al 39 described nine complications involving cerebral and extracerebral haemorrhages (out of 25 procedures), a more recent study, 42 had contradictory conclusions with a very low rate of haemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%
“…34 Cardiology studies showed that patients who receive prasugrel exhibit major haemorrhages more frequently than patients who receive clopidogrel, especially in patients with previous strokes, elderly patients (more than 75 years) and slim patients (weight lower than 60 kg). 33,35 However, the increased risks associated with prasugrel were not found in other cardiology series, 36,37 Until now, usage of prasugrel in Interventional Neuroradiology 23 (1) cerebrovascular diseases field has been limited 16,[38][39][40][41][42] by the fear of risk of intracranial haemorrhage. While Akbari et al 39 described nine complications involving cerebral and extracerebral haemorrhages (out of 25 procedures), a more recent study, 42 had contradictory conclusions with a very low rate of haemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study showed prasugrel and clopidogrel to be similar in terms of adverse outcomes and bleeding events and the authors concluded that prasugrel was equally effective and safe [ 27 ]. This result was different from ours in terms of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Main difference with clopidogrel is a more reliable conversion to the active drug and more rapid onset of action than clopidogrel. Moreover, genetic polymorphisms do not influence efficacy of prasugrel [59]. Ticagrelor is a new generation of reversible inhibitors of the P2Y12 receptor.…”
Section: Antiplatelet Agentsmentioning
confidence: 99%